2021
DOI: 10.1108/dprg-11-2020-0159
|View full text |Cite
|
Sign up to set email alerts
|

Digital sustainability: how information and communication technologies (ICTs) support sustainable development goals (SDGs) assessment in municipalities

Abstract: Purpose This paper aims to discuss the role of information and communication technologies (ICTs) in the effective assessment of the sustainable development goals (SDGs) related to smart and sustainable city initiatives. Design/methodology/approach The study is based on a systematic review of the literature within the Web of Science and Scopus databases, comprising the studies about ICTs related to smart and sustainable city initiatives and sustainable assessment. Findings The main results point out that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 72 publications
0
5
0
2
Order By: Relevance
“…Thanks to the radical decrease in the cost of collecting, storing, and processing information ( Wysokińska, 2021 ), DT offers LGs the potential to achieve SDGs by providing managers with valuable information to establish programs for the progress and improvement of citizenship ( Mantovani-Ribeiro et al, 2021 ). Therefore, DT generates a favorable context for constructing sustainable communities by efficiently and sustainably managing data and digital information ( ElMassah & Mohieldin, 2020 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Thanks to the radical decrease in the cost of collecting, storing, and processing information ( Wysokińska, 2021 ), DT offers LGs the potential to achieve SDGs by providing managers with valuable information to establish programs for the progress and improvement of citizenship ( Mantovani-Ribeiro et al, 2021 ). Therefore, DT generates a favorable context for constructing sustainable communities by efficiently and sustainably managing data and digital information ( ElMassah & Mohieldin, 2020 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For instance, the existing literature on SDGs is investigating factors that increase SDG practices (Santos and Bastos 2020); for instance, scalable solutions to SDGs through social entrepreneurship (Goyal et al 2020), the role of ISO (Khan et al 2021d;Toha et al 2020), environmental policy (Coscieme et al 2021), the implication of SDGs' sustainable reporting (Calabrese et al 2021), and firms' contribution through community partnerships over SDGs have been studied, with a majority of positive outcomes (Ordonez-Ponce et al 2021). The literature also contains studies that have investigated the effect of the industrial revolution on IoTs such as digital sustainability contribution (Ribeiro et al 2021), digitalization and integration (Onyango and Ondiek 2021), Big Data (Hassani et al 2021), and blockchain (Parmentola et al 2021) in promoting sustainable development goals amongst firms. In addition, the literature also shows data at the country level and indicates a significant positive relationship amongst SDGs (Pradhan et al 2017).…”
Section: Nexus Of Sustainable Development Goals Practice and Firms' F...mentioning
confidence: 99%
“…Fintech is an interlink between finance and technology, which refers to digital innovation to improve, develop, and automate financial services to promote and support enterprises, business owners, and investors in managing their financial activities [1][2][3]. Fintech and information communication technology (ICT) have been cited as the main drivers of financial inclusion in recent research [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the novelty and contributions of our research are as follows: (1) The impact of behavioral characteristics on crowd investors' intention, which is currently a gap in developing countries like Pakistan [31], utilizing a large primary dataset that includes most of Pakistan's provinces, is a distinctive aspect of this study. (2) Using the lens of the theory of planned behavior (TPB) by [32], the majority of studies observed TPB's predictive power on online purchases [33][34][35], but only a few investigated the TPB linked to investor intention in crowdfunding [5,34,36,37], with an additional factor of trust that strengthens the role of the platform in consumer decision making [38][39][40][41][42], which is rarely used in literature, especially in a developing country context. (3) Platform-related factors of crowdfunding with the addition of blockchain technology as an additional factor affecting investors' trust for investing in a crowdfunding platform.…”
Section: Introductionmentioning
confidence: 99%